Continuous Multimodality Monitoring in Children after Traumatic Brain Injury-Preliminary Experience. - Adam M H Young; Joseph Donnelly; Marek Czosnyka; Ibrahim Jalloh; Xiuyun Liu; Marcel J Aries; Helen M Fernandes; Matthew R Garnett; Peter Smielewski; Peter J Hutchinson; Shruti Agrawal (PLoS ONE)
Introduction Multimodality monitoring is regularly employed in adult traumatic brain injury (TBI) patients where it provides physiologic and therapeutic insight into this heterogeneous condition. Pediatric studies are less frequent. Methods An analysis of data collected prospectively from 12 pediatric TBI patients admitted to Addenbrooke's Hospital, Pediatric Intensive Care Unit (PICU) between August 2012 and December 2014 was performed. Patients' intracranial pressure (ICP), mean arterial pressure (MAP), and cerebral perfusion pressure (CPP) were monitored continuously using brain monitoring software ICM+®,) Pressure reactivity index (PRx) and 'Optimal CPP' (CPPopt) were calculated. Patient outcome was dichotomized into survivors and non-survivors. Results At 6 months 8/12 (66%) of the cohort survived the TBI. The median (±IQR) ICP was significantly lower in survivors 13.1±3.2 mm Hg compared to non-survivors 21.6±42.9 mm Hg (p = 0.003). The median time spent with ICP over 20 mm Hg was lower in survivors (9.7+9.8% vs 60.5+67.4% in non-survivors; p = 0.003). Although there was no evidence that CPP was different between survival groups, the time spent with a CPP close (within 10 mm Hg) to the optimal CPP was significantly longer in survivors (90.7±12.6%) compared with non-survivors (70.6±21.8%; p = 0.02). PRx provided significant outcome separation with median PRx in survivors being 0.02±0.19 compared to 0.39±0.62 in non-survivors (p = 0.02). Conclusion Our observations provide evidence that multi-modality monitoring may be useful in pediatric TBI with ICP, deviation of CPP from CPPopt, and PRx correlating with patient outcome.